2014
DOI: 10.1159/000433520
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Continuous Constant Light Alters Endochondral Ossification of the Tibiae of Rat Pups

Abstract: Clinical and experimental studies suggest that prenatal exposure to stress can impact the growth and development of offspring. The effect of prenatal exposure to constant light, applied as a chronic stressor, on endochondral ossification of the tibiae of 3-day-old and 15-day-old pups was histomorphometrically evaluated. Pregnant rats were divided into 2 groups: mothers chronically exposed to a 12:12-hour light/light cycle (LL) and control mothers maintained on a 12:12-hour light/dark cycle on days 10-20 of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…10 -11 Dancause et al have reported prenatal stress results in shorter long bones in adulthood, independently of effects on overall body size. 24 The present study adds to a growing body of evidence suggesting prenatal stress is a risk factor for not only poor linear growth of bones as earlier reported, 23,25 but also the overall postnatal physical development of the pups. Maternal stress retards foetal development in rats with delay in the postnatal milestones.…”
Section: Discussionsupporting
confidence: 70%
“…10 -11 Dancause et al have reported prenatal stress results in shorter long bones in adulthood, independently of effects on overall body size. 24 The present study adds to a growing body of evidence suggesting prenatal stress is a risk factor for not only poor linear growth of bones as earlier reported, 23,25 but also the overall postnatal physical development of the pups. Maternal stress retards foetal development in rats with delay in the postnatal milestones.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, disruption of the light/dark cycle during pregnancy has been associated with adverse outcomes, such as a higher risk of pre-term birth, low birth weight babies, spontaneous abortion and subfertility (Knutsson 2003;Mahoney 2010). Recent animal studies have shown that exposure to continuous light during pregnancy is a good model for development of neuropsychiatric disorders and developmental alterations such as cardiovascular dysfunction and skeletal defects in the offspring (Fontanetti et al 2014;Galdames et al 2014;Voiculescu et al 2016). However, under continuous light, the circadian clock is free running, and the question remains open to what extent the circadian system is disturbed by chronic stress, rather than CRD.…”
Section: Introductionmentioning
confidence: 99%